Lost Evangeline - DiCamillo, Kate (DiCamillo, Kate. Norendy tale., 2025)
When a shoemaker discovers a tiny girl (as small as a mouse!) in his shop, he takes her in, names her Evangeline, and raises her as his own. The shoemaker's wife, however, fears that Evangeline has bewitched her husband, so when an opportunity arises to rid herself of the girl, she takes it. Evangeline finds herself far from her adopted father and her home, a tiny girl lost in the wide world. But she is brave, and she is resourceful, and with the help of those she meets on her journey -- including a disdainful and self-satisfied cat -- she may just find her way again. Return to the magical land of Norendy in this third original fairy tale by renowned storyteller Kate DiCamillo, perfect for savoring alone or for reading aloud with someone you love. Graced with exquisite black-and-white illustrations by Sophie Blackall, this timeless story of a girl and her father will make you believe in the impossible.